Exploring the suitability of electric vehicles in the United States. (15th February 2017) - Onat, Nuri C.; Noori, Mehdi; Kucukvar, Murat; Zhao, Yang; Tatari, Omer; Chester, Mikhail
Abstract: This study explores suitability of battery electric vehicles in the United States by considering their potential market share and operations costs as well as the state-specific variations in electricity generation profiles, given current government policies and the social acceptability of the technology. A performance assessment is developed to compare each state and identify major policy efforts that are needed to increase the environmental and economic competitiveness of electric vehicles. A novel multi-criteria decision-support framework, integrating Life Cycle Assessment, Data Envelopment Analysis, and Agent Based Modeling, is developed. To this end, the environmental and economic impacts of battery electric vehicles are calculated based on three scenarios: an average electricity generation mix, a marginal electricity generation mix, and a solely renewable energy mix with 100% solar. The states are classified, each requiring different policy strategies, in accordance with their performance scores. The results provide important insights for advancing transportation policies and a novel framework for multi-criteria decision-making in the future analyses. Abstract : Environmental and economic impacts of Battery Electric Vehicles are assessed. States are benchmarked based on their performances. A novel decision making framework is proposed. State-specific policy recommendations are proposed for electric vehicle adoption. Most of the states in the west coast of the U.S. need immediate action.